ChemInform Abstract: An Efficient Catalyst‐Free Synthesis of Novel Benzo[a][1, 3]oxazino[6, 5‐c]phenazine Derivatives via One Pot Four‐Component Domino Protocol in Water. Issue 16 (April 2015) - Khanna, Garima; Chaudhary, Ankita; Khurana, Jitender M.
Abstract The reaction process is ecofriendly and economical.